The - Miller, Roger LeRoy (Delmar Cengage Learning, 2009)
The text gives the student a thorough introduction to not only the legal system in general, but to specific areas of the law and the paralegal's integral role as a member of the legal team. The student gains a comprehensive understanding of the laws in our society, the importance of ethical and professional responsibility, and the skills needed to thrive in this environment. Technology features, including spotlights on how technology is changing litigation, legal research, and overall office management, convey the importance of developing strong skills in this area. "Paralegal Profiles" and "Featured Guests" bring a personal touch to the material - as students learn how professionals truly work in each area of the law and how each skill directly translates on-the-job